Formação continuada de professores para as práticas de língua inglesa : uma proposta itinerante - Lima, Antonio Marcos da Cruz (2020)
This current research takes part in the Graduate Program in Education of Social and Human Sciences Institute of the Federal University of Mato Grosso, university campus of Rondonópolis (PPGEdu/UFMT/CUR), in the line of research Teachers ́ Education and Educational Public Policies, and it is inserted in the research group called InvestigAção, in which the Observatory of Education (OBEDUC) was bounded until 2017, remaining its educational actions so far, in which beginner teachers, experienced ones from public school system, Pedagogy undergraduates and Master degree students in Education PPGEdu/UFMT participate. This study investigates the English Language inclusion for children in the early years of the elementary school, specifically in the second cycle (4th and 5th years). The concern establishes regarding the teacher's knowledge in relation to the content that is being taught in the municipal school in Rondonópolis/MT, since, it is the pedagogue teacher who teaches this discipline without, however, having received the education for teaching the referred idiom while graduating student in Pedagogy. Thus, it is a great challenge, causing anxiety and concerns. In this sense, the aim of this research is to investigate if the itinerancy in the English Language offer provided for the teachers in their own teaching environment, favor, beyond a significant learning, their continuity over the referred mini course. The methodology is qualitative inserted in the research-formation. For data collection, we used the semi-structured interviews and the field journal reports of both the participant teachers and the researcher. We used ddocumentary analysis of official documents regarding the inclusion of the English language in the curriculum in the early years of elementary school, as well as the teachers ́ education of that language. The results reveal that, the course being offered at the school, where the participants pursue their professionalism, makes engagement and learning more effective, as they are all at the same linguistic level and share the same challenges and feelings when dealing with the English language.